THE MIDDLE HELLADIC FINE GRAY BURNISHED (GRAY MINYAN) SEQUENCE AT MITROU, EAST LOKRIS. - Hale, Christopher M. (Hesperia)
A preliminary, seven-phase Fine Gray Burnished (Gray Minyan) ceramic sequence has been developed at Mitrou, East Lokris, spanning the whole of the Middle Helladic period. Grounded in detailed stratigraphy from two different excavation areas, this ceramic sequence provides the first pottery chronology of its kind for Middle Helladic central Greece. By using quantitative analysis, the frequency of individual feature types has been determined for significant deposits, and distinct patterns of development over time can be observed. This sequence significantly increases our understanding of Fine Gray Burnished development within this important region and greatly improves the accuracy of relative dating methods in the immediate area.